Kompetencje współczesnego nauczyciela - Strykowski, Wacław (Wydawnictwo Naukowe UAM Poznań, 2005)
The article defines competences as a harmonic composition of knowledge, ability to understand and desire. Different kinds of contemporary teacher competences are discussed, based on pedagogical literature. Next, some competence areas are described as proposed by the author. Those are the following competences: 1) substantial, 2) psychological-pedagogical, 3) diagnostic, 4) designing, 5) didactic-methodic, 6) communicative, 7) medial, 8) evaluative, 9) to assess curricula and course books, 10) self-educational.
Competences of contemporary teacher